RESPONSIBILITY OF MONKS IN THE CONTEXT OF LAW AND SOCIETY - Gligić, Sanja (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2021)
Over the course of history, human will invaded ecclesiastical life, wishing to get a strong foothold therein. Since Emperor Constantine’s era, the idea matured in the ecclesiastical consciousness according to which the fundamental principle behind the organization of ecclesiastical lifestyle belonged to the domain of the law. Nevertheless, in contrast to positive law, canon law does not constitute an expression of the will of an individual or congregation, and instead comprises rules deriving from the nature of the Church. Since the Church is, just like any other organism, governed by two tenets – that of organization which is static, and its life function which is dynamic – the responsibility of monks can be perceived either in line with canonic law or within the social context. In so doing, these tenets are inalienable since there can be no life without organization, nor can there be organization without life.Positive law prescribes that in the event that a member abandons an organization, regardless of the reasons behind such action (be it voluntary or through the power of law), all ties between the said organization and its former member are to be broken. On the other hand, in the event that a penalized monk has to leave the monastery due to the gravity of the pronounced sanction, as its former member he is to preserve the status of a Christian. This point derives from the fact that baptism constitutes an indelible fact of spiritual life.In the paper, the matter of the responsibility of monks is examined by means of a comparison between mediaeval and contemporary sources of the Serbian canon law in view of identifying changes in the said period and drawing the most accurate conclusions therein.
Keywords: monk; sanction; disciplinary-criminal jurisdiction; responsibility; typika of St. Sava; decree on monastic life